PENGARUH KEMAMPUAN KERJA (WORK ABILITY) DAN KUALITAS KERJA (WORK QUALITY) TERHADAP KUALITAS PELAYANAN PUBLIK DIDINAS SOSIAL KABUPATEN BANGKALAN - Iman Muazansyah (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2018)
The problem of quality of human resources is an important thing in realizing a quality public service. The role of human resources, especially the government apparatus, is important in improving the quality of public services provided to the community. This study aims to analyze the effect of Work Ability (work ability) and Quality Work (work quality) on the quality of public services at the Office of Social Affairs Bangkalan. This research uses explanatory research type with quantitative approach. Samples taken are employees of Bangkalan District Social Service counted 98 people. Data collection was done by distributing questionnaires. Data analysis technique used is Structural Equation Modeling (SEM) with Partial Least Square (PLS) program. The results of this study indicate that work ability and work quality have a significant influence on the quality of public services in Bangkalan District Social Service.